2023
DOI: 10.21680/2176-9036.2023v15n1id28150
|View full text |Cite
|
Sign up to set email alerts
|

Accrualls e risco sistemático nas empresas brasileiras

Abstract: Objetivo: Investigar se o risco sistemático das empresas listadas na Bolsa de valores brasileira (B3) é afetado pela qualidade das informações contábeis. Adicionalmente, verificou-se se o risco sistemático foi afetado de forma diferente após a obrigatoriedade da adoção das IFRS no Brasil. Metodologia: A amostra compreendeu todas as empresas com observações listadas na bolsa de valores brasileira (B3) do período de 2005 a 2021. Foi realizada pesquisa empírica com análise descritiva e enfoque quantitativo. Os da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
2
0
0
Order By: Relevance
“…As for discretionary accruals, the second proxy for accounting information quality, Table 2 shows a mean of -0.0012, providing evidence that this earnings management strategy has been used more to reduce company profits, contrary to those that were exposed by Santana et al (2020). Moreover, it is verified that the income management by discretionary accruals showed high heterogeneity, suggesting that the companies in the sample have different levels regarding the quality of their information, which may be a factor that explains the high oscillation verified in systematic risk, corroborating what was found by Oliveira Junior et al (2023).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…As for discretionary accruals, the second proxy for accounting information quality, Table 2 shows a mean of -0.0012, providing evidence that this earnings management strategy has been used more to reduce company profits, contrary to those that were exposed by Santana et al (2020). Moreover, it is verified that the income management by discretionary accruals showed high heterogeneity, suggesting that the companies in the sample have different levels regarding the quality of their information, which may be a factor that explains the high oscillation verified in systematic risk, corroborating what was found by Oliveira Junior et al (2023).…”
Section: Resultssupporting
confidence: 80%
“…Thus, there is evidence that earnings management by discretionary accruals positively influences systematic risk, not rejecting the second subhypothesis (H1b). These findings are convergent with those of Moura et al (2015), Xing andYan (2019), andOliveira Junior et al (2023) and divergent from the results found by Nardi et al (2009).…”
Section: Variablesupporting
confidence: 58%